Correlation between Physical Activity Level and Health–Related Quality of Life among Elderly - Ricky Anguda; Setiawan Setiawan; Irma Ruslina Defi (Althea Medical Journal, 2016)
Background: The elderly population will keep growing in Indonesia. Decreased body function in elderly will affect their health–related quality of life. The aim of this study was to know the correlation between physical activity level and health–related quality of life among elderlyMethods: A cross-sectional analytical study was conducted from September to November 2014 in Panti Sosial Tresna Wredha Budi Pertiwi. The level of physical activity was measured with General Practice Physical Activity Questionnaire (GPPAQ) and health–related quality of life using the 36–Item Short Form Health Survey version 2 (SF–36v2). There were 14 out of 29 female elderly who met the inclusion criteria. The data were collected using validated questionnaires and tested with simple linear regression.Results: The physical activity level includes one inactive, three moderately inactives, eight moderately actives, and two actives. The average score of the health–related quality of life was 41.121±8.88 for the physical component scale (below average) and 57.629±7.54 (above average) for the mental component scale. No significant correlation was found between the level of physical activity with the physical component scale (p–value = 0.731) and mental component scale (p–value = 0.901).Conclusions: The most frequently found physical activity level is the moderately active level. The score for the physical component scale is under average, while the mental component scale is above average. There is no correlation between the physical activity level and health–related quality of life for the physical component scale and the mental component scale. [AMJ.2016;3(3):405–10]DOI: 10.15850/amj.v3n3.890